2007
DOI: 10.1523/jneurosci.1863-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Breadth of Tuning and Taste Coding in Mammalian Taste Buds

Abstract: A longstanding question in taste research concerns taste coding and, in particular, how broadly are individual taste bud cells tuned to taste qualities (sweet, bitter, umami, salty, and sour). Taste bud cells express G-protein-coupled receptors for sweet, bitter, or umami tastes but not in combination. However, responses to multiple taste qualities have been recorded in individual taste cells. We and others have shown previously there are two classes of taste bud cells directly involved in gustatory signaling:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
271
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(292 citation statements)
references
References 37 publications
18
271
3
Order By: Relevance
“…Similarly, solitary nasal chemosensory cells coexpress Tas1R3 with Tas2R5 and Tas2R8 (33); however, although the responses of these cells to bitter stimuli are well documented (34), whether they also respond to umami remains to be established. This situation is in contrast to oropharyngeal gustation, where Tas1R and Tas2R receptors are not coexpressed in taste buds (33,35), and 83% of receptor cells in murine vallate papillae respond to only a single taste quality, which provides a basis for taste coding in taste buds (36). ] i recordings from eGFP + (n = 13, Upper) and eGFP − (n = 74; Lower) isolated urethral cells located in their vicinity (same field of view during confocal laser scanning recording) on the coverslip.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, solitary nasal chemosensory cells coexpress Tas1R3 with Tas2R5 and Tas2R8 (33); however, although the responses of these cells to bitter stimuli are well documented (34), whether they also respond to umami remains to be established. This situation is in contrast to oropharyngeal gustation, where Tas1R and Tas2R receptors are not coexpressed in taste buds (33,35), and 83% of receptor cells in murine vallate papillae respond to only a single taste quality, which provides a basis for taste coding in taste buds (36). ] i recordings from eGFP + (n = 13, Upper) and eGFP − (n = 74; Lower) isolated urethral cells located in their vicinity (same field of view during confocal laser scanning recording) on the coverslip.…”
Section: Discussionmentioning
confidence: 91%
“…While it has been reported that bitter and sweet things stimulate the Type II receptor cells, which have G-protein-coupled taste receptors and similar signaling pathways, 7) it has also been proposed that this type of receptor cell may not participate in the recognition of sour taste. 8) In fact, Type III taste cells are necessary for the recognition of sour taste. 9,10) From our results, it can be postulated that sour stimuli, which have a different pathway from bitter or sweet stimuli, may be important for bitterness suppression.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we successfully verified the expression of nesfatin-1 in the type 2 taste buds of rat CV by immunohistochemical staining. It is reported that type 2 taste cells transduce sweet, bitter, or umami stimuli [29], and utilize a G protein-coupled transduction cascade for signaling [30,31]. This result provides insights into the distinct functions of NUCB2/nesfatin-1 within the gustatory system, and suggests it has the potential to influence the amounts and types of food ingested.…”
Section: Discussionmentioning
confidence: 99%